2022
DOI: 10.2519/jospt.2022.10802
|View full text |Cite
|
Sign up to set email alerts
|

Roland-Morris Disability Questionnaire, Oswestry Disability Index, and Quebec Back Pain Disability Scale: Which Has Superior Measurement Properties in Older Adults With Low Back Pain?

Abstract: General rightsCopyright and moral rights for the publications made accessible in the public portal are retained by the authors and/or other copyright owners and it is a condition of accessing publications that users recognise and abide by the legal requirements associated with these rights.• Users may download and print one copy of any publication from the public portal for the purpose of private study or research. • You may not further distribute the material or use it for any profit-making activity or commer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
17
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 51 publications
2
17
0
3
Order By: Relevance
“…The comparison between Groups I and II after injection showed no significant difference (p>0.05) regarding LBP VAS and RMQ and ODI scores. This finding is consistent with that reported by Wu et al 14 who compared intra-articular injections of PRP and CS for the treatment of lumbar FJ disease in a prospective study carried on 46 patients. The mentioned study showed that both groups demonstrated statistically comparable improvements in VAS, RMQ, and ODI scores.…”
supporting
confidence: 93%
See 2 more Smart Citations
“…The comparison between Groups I and II after injection showed no significant difference (p>0.05) regarding LBP VAS and RMQ and ODI scores. This finding is consistent with that reported by Wu et al 14 who compared intra-articular injections of PRP and CS for the treatment of lumbar FJ disease in a prospective study carried on 46 patients. The mentioned study showed that both groups demonstrated statistically comparable improvements in VAS, RMQ, and ODI scores.…”
supporting
confidence: 93%
“…This tool has a total score of 24, with a score of 0 representing no disability and a score of 24 representing maximum disability. 14 The Oswestry Disability Index (ODI) has been considered as the gold standard for measuring degree of disability and estimating quality of life in a patient with LBP. 13 The ODI comprises 10 items that reflect the patient's ability to manage their everyday life while dealing with their pain.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…There is some debate about the best measure for LBP‐related disability (Chiarotto et al, 2016; Kent et al, 2015). The RMDQ has been shown to have adequate measurement properties in a range of domains as well as good test–retest reliability (Jenks et al, 2022; Lauridsen et al, 2006); it is particularly suited to studies in primary care populations (Lauridsen et al, 2006) and is one of the recommended core outcome measures for use in non‐specific LBP RCTs (Chiarotto et al, 2018). Measurement error is at random (Jenks et al, 2022) and therefore any bias is likely to result in an underestimate of pain‐related disability, so we are confident that the relationships reported in this study are not exaggerated.…”
Section: Discussionmentioning
confidence: 99%
“…The RMDQ has been shown to have adequate measurement properties in a range of domains as well as good testretest reliability (Jenks et al, 2022;Lauridsen et al, 2006); it is particularly suited to studies in primary care populations (Lauridsen et al, 2006) and is one of the recommended core outcome measures for use in non-specific LBP RCTs (Chiarotto et al, 2018). Measurement error is at random (Jenks et al, 2022) and therefore any bias is likely to result in an underestimate of pain-related disability, so we are confident that the relationships reported in this study are not exaggerated. Although there were participants with severe depressive symptom scores and high perceived stress scores, it is possible that the very fact they participated in the trial may mean that they represent a more motivated cohort than the general LBP population with depression and stress (Axén & Leboeuf-Yde, 2013).…”
Section: Strengths and Limitationsmentioning
confidence: 99%